Discharge Planning Kepatuhan Minum Obat Pada Pasien Gagal Jantung Kongestif di Rumah Sakit TK II Putri Hijau Medan - Vinky Wi Sheti Sinaga; Rani Sartika Dewi; AdeIrma Khairani (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Congestive heart failure is a physiological condition in which the heart cannot pump enough blood to meet the body's metabolic needs. The number of deaths caused by congestive heart failure in the world is 17.9 million people. The prevalence of congestive heart failure in Indonesia is 98,336 people. The prevalence of congestive heart failure in North Sumatra is 55,351 people. One of the causes is due to non-adherence of patients taking medication. Efforts that can be made to improve adherence to taking medication are the provision of discharge planning. This research method is a descriptive study with a case study design covering the stages of assessment, diagnosis, intervention, implementation and evaluation in two congestive heart failure patients at TK II Putri Hijau Medan Hospital. The results of the study were obtained after administering the discharge planning medication adherence to clients I and II clients taking medication 3x1 days regularly, the patient knows the correct principles of taking medication. The conclusion from the results of this study is that discharge planning is effective in increasing medication adherence in congestive heart failure patients. Suggestions from researchers to encourage people with congestive heart failure to adhere to taking medication. Keywords: Discharge Planning, Medication Compliance, Congestive Heart Failure ABSTRAK Gagal jantung kongestif adalah kondisi fisiologis dimana jantung tidak dapat memompa darah yang cukup untuk memenuhi kebutuhan metabolik tubuh. Jumlah kematian yang disebabkan oleh gagal jantung kongestif di dunia sebanyak 17,9 juta orang. Prevalensi gagal jantung kongestif di Indonesia sebesar 98.336 orang. Prevalensi gagal jantung kongestif di Sumatera Utara sebesar 55.351 orang. Salah satu penyebabnya adalah karena ketidak patuhan pasien minum obat. Upaya yang dapat dilakukan untuk meningkatkan kepatuhan minum obat yaitu pemberian Discharge planning. Metode penelitian ini adalah penelitian deskriptif dengan rancangan studi kasus meliputi tahapan  pengkajian, diagnosa, intervensi, implementasi dan evaluasi pada dua pasien gagal jantung kongestif di Rumah Sakit TK II Putri Hijau Medan.  Hasil penelitian  didapatkan setelah  pemberian  discharge planning  kepatuhan minum obat pada klien I dan II klien minum obat 3x1 hari secara teratur, pasien mengetahui prinsip benar minum obat. Kesimpulan dari hasil penelitian ini adalah pemberian discharge planning efektif dalam meningkatkan  kepatuhan minum obat pada pasien gagal jantung kongestif. Saran dari peneliti agar menganjurkan penderita gagal jantung kongestif untuk patuh minum obat. Kata Kunci: Discharge Planning, Kepatuhan Minum Obat, Gagal Jantung Kongestif